Kansas high school band directors and college faculties' attitudes towards teacher preparation in jazz education - Treinen, Craig Michael (Kansas State University, 2011)
The purpose of this study examined high school band directors and college music educators’ attitudes in regard to implementing curricula requirements for music teacher training programs in jazz education, as well as personal and professional characteristics to current and past jazz cultures in music education. In addition, high school band directors and college music educators were also asked to evaluate specific teaching skills and competencies necessary for preparing music education students to teach jazz as an essential part of their teaching responsibilities in Kansas’ schools. Primary participants in this study included high school band directors (N=175) randomly selected from each of the six districts based upon geographical location in Kansas: (1) Northeast, (2) North-central, (3) Northwest, (4) Southeast, (5) Southcentral, and (6) Southwest, and college music educators (N=50) from eight Kansas institutions that were members of the National Association of Schools of Music (NASM), and offer degrees in music education. The survey in this study used modified questions and statements that focused on teaching instead of performance as highlighted in an existing research instrument by Walter Barr (1974), “The Jazz Studies Curriculum.” Data compared between both studies revealed similar findings. A descriptive method of research was used and designed to provide structured responses. The survey was divided into five sections, included frequencies, rating scales, mean scores, yes-no questions and 3-point Likert type questions. Data collected from this study described the following: background characteristics, teaching skills and experiences, competencies for music education majors, and jazz education as it relates to teacher preparation in Kansas. Results from this study indicated that high school band directors and college music educators agreed that the current music education programs in Kansas were not preparing music education majors to teach jazz in the public schools. Respondents were asked to provide opinions related to jazz and jazz course requirements for music education majors graduating and applying for teacher certification. Respondents were also asked to provide statistical information regarding the prioritization of courses in jazz pedagogy, jazz ensemble, jazz history, jazz theory, jazz keyboard and jazz improvisation with regards to essential skills and competencies needed for public school teaching. Tables were utilized to show statistical data and comparisons. Implications from this study included the need for more teacher preparation in jazz education.
Keywords: Jazz; Education; Music Education (0522)